Research Trends in Underground Hydrogen Storage: A Bibliometric Approach - Barbara Uliasz-Misiak; Jacek Misiak; Radosław Tarkowski (Energies)
This article presents the findings of a bibliometric analysis of scientific publications in journals and materials indexed in the SCOPUS and Web of Science databases, covering the broad topic of underground hydrogen storage (UHS). The use of VOSviewer software for keyword analysis enabled the identification of four key research areas related to UHS. These areas include hydrogen and hydrocarbon reservoir engineering; hydrogen economy and energy transformation; processes in hydrogen storage sites, including lessons from CO2 sequestration; and the geology, engineering, and geomechanics of underground gas storage. The interdisciplinary nature of UHS research emphasises the synergy of research across diverse fields. A bibliographic analysis allowed for the identification of areas of intensive research and new directions of work related to UHS, key research centres, and the dynamics of the development of research topics related to UHS. This study revealed the chronological dispersion of the research results, their geographical and institutional variability, and the varying contributions of major publishing journals. The research methodology used can serve as an inspiration for the work of other researchers.